Jane Austen i Elizabeth Bennet – o wizerunku kobiecości w wybranych adaptacjach filmowych Dumy i uprzedzenia - Pilawska-Gronostaj, Roksana (Kultura-Społeczeństwo-Edukacja, 2024)
Aim: The article attempts a multifaceted analysis of the portrayal of female characters in selected film adaptations of Jane Austen’s novel Pride and Prejudice. Problem: The primary goal of the article was to address two research questions: how the world created by the author has been translated into the audiovisual realm of film, and whether, amidst changes in socio-cultural perceptions of women’s roles from the 1940s to contemporary times, the visual and characterological traits of the film’s main character, Elizabeth Bennet from Jane Austen’s novel, have also evolved. Method: Utilizing content analysis techniques, the study interpreted the depiction of the main character from three selected film adaptations created in different time periods – the 1940s, the 1990s, and the first decade of the 21st century. Results: The analysis indicates that the chosen film adaptations of Pride and Prejudice from 1940, 1995, and 2005 employ diverse patterns, cultural currents, and ideologies in shaping the main female character – ranging from typical screwball comedy, through classical British adaptations incorporating sexual aspects of the characters presented, to a romantic view of literary models. The 1995 BBC adaptation, by introducing feminist elements and highlighting Elizabeth Bennet’s personality, played a crucial role in altering the approach to adapting literary classics for the screen. In contrast, the 2005 version directed by Joe Wright focuses on the internal transformations of the characters, emphasizing their emotions and self-realization, thereby aligning more with contemporary audience expectations.